Three-year Outcomes of a Randomized Controlled Trial Comparing a 4.5-mm-Wide to a 3.75-mm-Wide Titanium Implant for Bone Conduction Hearing - Kruyt, Ivo J. (Otol Neurotol, 2018)
OBJECTIVE: To compare 3-year implant stability, survival, and tolerability of a 4.5-mm-wide (test) and a 3.75-mm-wide (control) percutaneous titanium implant for bone-conduction hearing, loaded with the sound processor after 3 weeks. METHODS: Sixty implants were allocated in a 2:1 ratio (test-control) in 57 adult patients included in this prospective randomized controlled clinical trial. Follow-up visits were performed at 7, 14, 21, and 28 days; 6 and 12 weeks; 6 months; and at 1, 2, and 3 years after implantation. During these visits, the implant stability quotient (ISQ) was measured by means of resonance frequency analysis (RFA). The peri-abutment soft tissue status was assessed according to the Holgers classification. Skin height around the abutment was evaluated. RESULTS: The mean area-under-the-curve (AUC) of ISQ-low was statistically significantly higher for the test implant (65.7 versus 61.4, p = 0.0002). Both implants showed high survival rates (97.4% versus 95.0%, p = 0.6374). Adverse soft tissue reactions were observed sporadically, with no significant inter-group differences. Skin thickening was seen in the majority of the patients, but no correlation with adverse soft tissue reactions or implant type was observed. CONCLUSION: The 4.5-mm-wide implant provides significantly higher ISQ values during the first 3 years after surgery compared with the previous generation 3.75-mm-wide implant. Both implants showed high survival rates and good tolerability. These long-term results indicate that the wider implant, loaded with a sound processor at 3 weeks, is a safe and well-performing option for hearing rehabilitation in specific types of hearing loss.